Two methodologies for brain signal analysis derived from Freeman Neurodynamics - Davis, Jeffery Jonathan Joshua; Kirk, Ian J.; Kozma, Robert (Frontiers in Systems Neuroscience, 2025)
Here, Freeman Neurodynamics is explored to introduce the reader to the challenges of analyzing electrocorticogram or electroencephalogram signals to make sense of two things: (a) how the brain participates in the creation of knowledge and meaning and (b) how to differentiate between cognitive states or modalities in brain dynamics. The first (a) is addressed via a Hilbert transform-based methodology and the second (b) via a Fourier transform methodology. These methodologies, it seems to us, conform with the systems' neuroscience views, models, and signal analysis methods that Walter J. Freeman III used and left for us as his legacy.